Phytochemical Profiling and Biological Activities of Strobilanthes urens (B. Heyne ex Roth) J.R.I. Wood. Leaf Extract (Acanthaceae) - T., Praveen; Kakkalameli, Siddappa B, (Sciences of Phytochemistry, 2025)
This study investigated the phytochemical composition and biological activities of Strobilanthes urens leaf extracts. The proximate composition, including protein, carbohydrate, lipid content, nutritive value, and total moisture, was evaluated. Qualitative phytochemical screening revealed the presence of alkaloids, flavonoids, proteins, tannins, phenols, terpenoids, saponins, glycosides, and carbohydrates in all three extracts, except for steroids in methanol, and both terpenoids and steroids in the distilled water extract. Alkaloids, tannins, saponins, glycosides, and steroids were absent in the chloroform extract. Quantitative analysis confirmed the presence of polyphenols, flavonoids, tannins, and alkaloids, while GC–MS analysis identified 22 major bioactive compounds with potential medicinal properties. Antioxidant activity assessed by the DPPH assay showed IC₅₀ values of 79.23 ± 3.78 µg/mL in methanol and 237.00 ± 12.37 µg/mL in distilled water, with no activity in chloroform. The extracts exhibited antibacterial activity but no significant antifungal effect. Cytotoxicity evaluation by MTT assay showed IC₅₀ values against MCF-7 and HepG2 cell lines ranging from 88.19 ± 8.29 to 188.10 ± 39.99 µg/mL. Overall, the findings highlight the phytochemical richness and potential pharmacological value of S. urens leaf extracts.